EGFR signaling in the HGG-02 glioblastoma cell line with an unusual loss of EGFR gene copy - Skoda, Jan; Neradil, Jakub; Zitterbart, Karel; Sterba, Jaroslav; Veselska, Renata (Oncology reports, 2014)
Epidermal growth factor receptor (EGFR) gene amplification and the overexpression of EGFR are described as common features of glioblastoma multiforme (GBM). Nevertheless, we previously reported the loss of EGFR gene copy in a GBM specimen from a patient with an unusually favorable course of the disease, and the HGG-02 cell line with this aberration was successfully derived from this tumor. Here, we present a detailed analysis of changes in gene expression and cell signaling in the HGG-02 cell line; the GM7 reference cell line with a standard EGFR gene copy number derived from a very aggressive GBM was used as a control. We confirmed the downregulation of EGFR expression and signaling in HGG-02 cells using different methods (RTK analysis, gene profiling and RT-PCR). Other changes that may have contributed to the non-aggressive phenotype of the primary tumor were identified, including the downregulated phosphorylation of the Axl and Trk receptors, as well as increased activity of JNK and p38 kinases. Notably, differences in PDGF signaling were detected in both of these cell lines; HGG-02 cells preferentially expressed and signaled through PDGFRα, and PDGFRβ was strongly overexpressed and phosphorylated in the GM7 reference cell line. Using expression profiling of cancer-related genes, we revealed the specific profile of HGG-02 cells that included upregulated tumor-suppressors as well as downregulated genes associated with the extracellular matrix. This study represents the first comprehensive analysis of gene expression and cell signaling in glioblastoma cells with lower EGFR gene dosage. As indicated by our results, the TAM receptors, Trk receptors and PDGFRs need to be investigated further since their regulation appears to be important for glioblastoma biological features as well as the clinical course of the disease.
Keywords: p38 Mitogen-Activated Protein Kinases; JNK Mitogen-Activated Protein Kinases; ErbB Receptors; erbB receptory; Cell Line, Tumor; Receptor Protein-Tyrosine Kinases; delece genu; Gene Dosage; nádorové buněčné linie; receptor trkA; nádory mozku; lidé; tyrosinkinasové receptory; signální transdukce; Proto-Oncogene Proteins c-sis; protoonkogenní proteiny; stanovení celkové genové exprese; Signal Transduction; mitogenem aktivované proteinkinasy p38; glioblastom; destičkový růstový faktor; Phosphorylation; Glioblastoma; JNK mitogenem aktivované proteinkinasy; Axl Receptor Tyrosine Kinase; Gene Deletion; fosforylace; Platelet-Derived Growth Factor; protoonkogenní proteiny c-sis; Brain Neoplasms; Proto-Oncogene Proteins; genová dávka; Gene Expression Profiling; tyrozinkinasový receptor AXL; Receptor, trkA; Humans